DEVELOPING LEARNING MATERIAL OF DESCRIPTIVE TEXT FOR THE TENTH GRADE STUDENTS AS A SUPPLEMENTARY MATERIAL - Frikson Siburian; Meisuri Meisuri; Sumarsih Sumarsih (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2017)
The objective of this study was to develop learning material on descriptive text based on the students’ needs as a supplementary material. This research was conducted as research and development (R & D) design. The data were taken from the books, internet and environment. The instruments used in this research were questionnaire and interview. The product of this study was a set of learning material that can be used as a supplementary material. The developed learning material consisted of two units, namely: Describing peoples which was consisted of two texts namely describing public figure (Jokowi Dodo) and describing an Idol (Agnes Monica) and Describing places consisted of three texts namely; Azizi mosque, Tangkahan and Bukit Lawang. Each of the text consisted of two kinds of exercise and in the last page of the product were provided the answer keys. Keywords: Reading Learning Material, Supplementary Material, Descriptive text.